Fast determination of minoxidil by photometric flow titration - de Sousa, Rogério Adelino; Semaan, Felipe Silva; Baio, José Augusto Fragale; Cavalheiro, Éder Tadeu Gomes (Eclética Química, 2005)
A photometric flow titration based on the redox reaction between KMnO 4 and minoxidil is described. The best titration results were observed at 3.20 x 10 -4 mol L -1 KMnO 4 and 1.00 x 10 -3 mol L -1 minoxidil, using the minoxidil solutions as titrant. The flow rate was fixed at 17 mL min -1 and the titrant was added to the system in aliquots of 500 μL, the color changes were monitored at 550 nm. The method was applied to commercial samples and compared with the results from a chromatographic procedure. Recoveries from 97.6 to 102.8 % were observed depending on the sample. Comparison with the chromatographic procedure reveled relative errors of 3.5 - 4.0 %.